МУҲАББАТ ТЕМАСЫН ЖЫРЛАЎДАҒЫ ХАЛЫҚЛЫҚ ДӘСТҮР МЕНЕН САБАҚЛАСЛЫҚ (Х.Даўлетназаров, Б.Сейтаев, О.Сәтбаев поэзиясы мысалында) - Смамутова, Ш.А. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of development of Karakalpak in poetry. The years of Independence on the basis of the analysis of the works of the poets Kh.Dauletnazarov, O.Satbaev, B.Seytaev. The author shows how the theme of love and folk motives are expressed in the creative work of the poets.
Keywords: reculiarities of lyrics; poetry of the Independence period; features individual style of poets; language of poetry; secrets of skill; love lyricism in the years of Independence